THE IMPLEMENTATION OF ISLAMIC LAW: THROUGH ISLAMIC LAW POLITICS AND NOT THROUGH TERRORISM - Suprajogo, Tjahjo (Journal of Islamic Law Studies, 2021)
In the context of Indonesia, empirically and historically there is no doubt that Islamic law is one important element in the formation of national law (positive law). Also, sociologically, Islam as a religious doctrine is to have religious values that have been believed by Muslims to be a system of life that is regarded as the law derived from religion by most Indonesian people. Judging from the scope of realistic politic or ideological-empiric, there is a serious debate in the formulation of the basic constitution of the country is currently taking place in the sessions Agency of Efforts Investi- gation for Indonesian Independence (BPUPKI), May 28-June 1, 1945 and July 10 to 17, 1945, and in the sessions of the Preparatory Committee for Indonesian Independence (PPKI) 18 to August 22, 1945, in the framework of the preparation and approval of the 1945 Constitution (Halim, Ahkam Journal, Vol. XIII, No. 2, July 2013, p. 260). Advanced implications of the ideological polemics are the pros and cons in the middle of the people in the realm of law regarding the implementation of Islamic law in Indonesia. Socio-politically, faced with the reality of the plurality of the Indonesian society is very complex, the response of Muslims themselves against the implementation of Islamic law in Indonesia, there are at least 3 (three) polarization. There are most of Muslims who want that Islamic law is substantive-formalistic enacted in regulation and legislation. There are others who believe that what an important is the values (moral ethics) of Islam entered in national law. While others, they just refuse altogether implementation of Islamic law. As far as the writer observation, that response in reality has given birth the diversity pattern of the struggle among Muslims such as a radical-psychic-physical approach demanding implementation of Islamic law in totality (kaaffah) with terror manner and acts. Even though when considering various aspects, such as the persistence of the variations and mozaic of thought Muslims on the relationship of the shari’a and the state, there are many law schools of thought (madzahib fiqh) related to the products of Islamic law, the configuration of socio-political determining the implementation of Islamic law, there are variables of social, cultural, political and history are diversities that influenced the formation of the law in various Islamic countries (Maula, Hermeneia, Journal of Islamic Studies at the Interdisciplinary Vol.2 No. 2 July-December 2003, p. 240), different practical application of Islamic law, and depend on who ruled government authority in the formulation and decision making. Departing from these reasons, the author would like to propose a recommendation that the actual implementation of Islamic law in Indonesia can be approached from a law politic approach of Islamic as a public policy-making process and not by means of terrorism.